UPAYA DIVERSI DALAM PROSES PERADILAN ANAK - Ramadhan, Hidayatullah; Eka Wisanjaya, I Gede Pasek (Kertha Wicara : Journal Ilmu Hukum; Vol. 03, No. 02, Mei 2014, 2014)
The title of this journal reads “Strive for Diversion in Process of Legal Proceeding at the Juvenile Court” it has purpose, to explain about process of children case in juvenile court.This journal uses normative legal writing method. In fact that over 4000 Indonesian children every year are brought to court for allegedly misdemeanours, such as theft. Commonly they don’t get legal aid from lawyer even social department. This is not suprising that 9 of 10 children has thrown into jail or prison. Therefore it needs strive for Diversion. Diversion is act to divert formal process of child case for allegedly have commited crime with or without requirement diversion approach could be applied in child case which is contrary to the law.
Keywords: Child, Diversion process, Juvenile court, Contrary to the law